The function of wing bullae in mayflies (Insecta: Ephemeroptera) reveals new insights into the early evolution of Pterygota - Dominguez, Eduardo (2023)
Background: Mayflies are basal winged insects of crucial importance for the understanding of the early evolution of Pterygota. Unlike all other insects, they have two successive winged stages, the subimago and the imago. Their forewings feature so-called bullae, which are desclerotized spots in the anterior main veins. Up to now, they have been considered to play a major role in wing bending during flight.Results: We investigated bullae by multiple methods to reveal their structure and arrangement and to gain new information on the evolution of insect flight. Bullae are mostly present in the anterior negative wing veins, disrupting the otherwise rigid veins. High-speed videography reveals that mayfly wings do not bend during flight. Likewise, different arrangements of bullae in different species do not correlate with different modes of flying. Observations on the moulting of subimagines unravel that they are essential for wing bending during the extraction of the imaginal wing from the subimaginal cuticle. Bullae define predetermined bending lines, which, together with a highly flexible wing membrane enriched with resilin, permit wing bending during subimaginal moulting. Bullae are only absent in those species that remain in the subimaginal stage or that use modified modes of moulting. Bullae are also visible in fossil mayflies and can be traced back to stemgroup mayflies of the Early Permian, the 270 million years old Protereismatidae, which most probably had bullae in both fore- and hind wings.Conclusions: Bullae in mayfly wings do not play a role in flight as previously thought, but are crucial for wing bending during subimaginal moulting. Thus, the presence of bullae is a reliable morphological marker for a subimaginal life stage, confirming the existence of the subimago already in Permian Protereismatidae. A thorough search for bullae in fossils of other pterygote lineages may reveal wheather they also had subimagines and at what point in evolution this life stage was lost. In mayflies, however, the subimago may have been retained due to selective advantages in connection with the transition from aquatic to terrestrial life or due to morphological requirements for a specialized mating flight.